2021
DOI: 10.3906/sag-2009-323
|View full text |Cite
|
Sign up to set email alerts
|

An alternative supplemental feeding method for preterm infants: the supplemental feeding tube device

Abstract: Çalışma minör düzeltme sonrası basılabilir. Değerli Editörüm, Makalemizi değerlendirdiğiniz için çok teşekkür ederiz. İstenilen düzeltmeleri gerçekleştirdik ve makale içinde sarı ile boyadık. İlginiz ve paha biçilmez desteğiniz için teşekkür eder, Saygılarımızı sunarız… 1 Tablo 1 altındaki p<0.05 kelimesinin çıkartılması, tablo 2 altındaki p<0.01 kelimesinin ve tablo 2de bunun karşılığının yanına tek asteriks konulması uygun olur. Tablo 1'in altındaki p<0.05 kelimesini çıkardık. Tablo 2'deki p<0.01 kelimesinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This qualitative study results showed that mothers had both positive and negative experiences with the use of an SFTD (Borucki, 2005). In a randomized control study conducted in Turkey with 46 preterm infants, there was no difference in timing of transitioning to breastfeeding for preterm infants fed using the SFTD versus bottle-fed infants (İncekar et al, 2021). Although SFTDs are commonly used, there are limited data on the breastfeeding efficacy or benefits to the mother or the infant (Penny et al, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…This qualitative study results showed that mothers had both positive and negative experiences with the use of an SFTD (Borucki, 2005). In a randomized control study conducted in Turkey with 46 preterm infants, there was no difference in timing of transitioning to breastfeeding for preterm infants fed using the SFTD versus bottle-fed infants (İncekar et al, 2021). Although SFTDs are commonly used, there are limited data on the breastfeeding efficacy or benefits to the mother or the infant (Penny et al, 2018).…”
Section: Introductionmentioning
confidence: 97%